Z badań nad tzw. horyzontem starosznurowym w rozwoju późnoneolitycznej kultury społeczeństw Kujaw - Kośko, Aleksander (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
The problem of the so-called pan-European horizon of the Corded Ware culture in Kuyavia, discussed here, is occasioned by the publication of an Early Corded Ware grave from Krusza Zamkowa. Bydgoszcz province, site 3 (Figs. I -3). The analysis of available sources associated with that horizon indicates that the set of attributes regarded as distinctive was in Kuyavia a constant component of the Funnel Beaker groups such as Eastern, Mątwy. Radziejów and so-called epi-Funnel-Beaker, differentiated chronologically and genetically. Thus the set was rather an indicator of the exogenous component generally associated with the area between the Vistual and the Dnieper, and playing an unspecified culture-forming role in the autogenesis of local communities. The fact remains that a large majority of local communities of the „classic” Corded Ware horizon show opposite genetic links, tending towards "Baltic" centres, notably those in the area between the lower Odra and the Elbe.